A facile way to fabricate double-shell pomegranate-like porous carbon microspheres for high-performance Li-ion batteries. Issue 24 (6th June 2017) - Zhang, Lei; Dou, Yuhai; Guo, Haipeng; Zhang, Binwei; Liu, Xiaoxiao; Wan, Min; Li, Weijie; Hu, Xianluo; Dou, Shixue; Huang, Yunhui; Liu, Huakun
Abstract : We report for the first time a facile preparation of double-shell pomegranate-like porous carbon microspheres (PCMs) by a modified templating technique. Abstract : We report for the first time a facile preparation of double-shell pomegranate-like porous carbon microspheres (PCMs) by a modified templating technique. The microsized PCMs are encapsulated within integrated carbon coating layers and composed of interconnected nanosized hollow carbon spheres, giving rise to a special double-shell structure. Calcium carbonate (CaCO3 ) is employed as the primary sacrificial template and acetylene as the carbon precursor via chemical vapor deposition (CVD). The PCMs exhibit an initial coulombic efficiency of 91% and a reversible capacity of 650 mA h g −1 at a current density of 200 mA g −1 after 500 cycles. Moreover, PCMs show excellent rate capability with capacities of 580 and 520 mA h g −1 at current densities of 1000 and 2000 mA g −1, respectively. The outstanding electrochemical properties of PCMs are originated from their unique structure. The inner interconnected porous carbon framework encapsulated by a self-supporting outer carbon coating shell provides more lithium ion storage sites, high electronic conductivity and fast ion diffusion. Most importantly, different from the previous studies, the introduction of the carbon coating layers on the outer surface of the whole microsphere can effectively strengthen the mechanical properties and prevent the electrolyte ingress, limiting the formation of extra solid–electrolyte interface films.